PENGARUH MOTIVASI DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KOPERINDAG KABUPATEN TANAH DATAR - Hafulyon Hafulyon; Muhammad Deni Putra; Khairulis Shobirin; Marda Elfisra (MABIS: Jurnal Manajemen Bisnis Syariah, 2021)
This study aims to determine how much influence motivation and work culture have on employee performance at the Koperindag office of Tanah Datar Regency. This type of research is field research (field research) with a quantitative approach. Motivation partially has a significant effect on employee performance. Work culture partially does not have a significant effect on employee performance. In silmutan, there is a positive and significant influence between motivation and work culture on employee performance at the Koperindag office of Tanah Datar Regency. Furthermore, the results of the study also showed that there was a positive and significant influence between motivation and work culture on employee performance at the Koperindag office of Tanah Datar Regency by 50.7%.